(untitled) (Bangladesh Journal of Urology, 2020)
Background:Among various intracorporeal lithotripters, Pneumatic lithotriptorhas become the widely used tool for the treatment of ureteric stones. Recently the Holmium:YAG laser has been used with a wide range of potential urological applications, including intracorporeal lithotripsy of ureteric stones. Objective: To compare the treatment of upper ureteric stone between laser and pneumatic lithotripsy. Materials and methods: One hundred patients with upper ureteric stone who underwent ureteroscopic lithotripsy in the Department of Urology, CMH, Dhakafrom October 2012 to September 2015 were enrolled in this study. Patients were divided into two groups. Group A (LL) were treated with holmium: YAG laser and Group B (PL) were treated with pneumatic lithotripsy. Two procedures were compared in term of stone fragmentation, stone clearance rate, duration of lithotripsy, complications and duration of post operativehospital stay. Patients were monitored as outpatients after one month and after three months with a kidney ureter and bladder radiograph and ultrasonograph. Patients with migrated fragments or incomplete clearance underwent an auxiliary procedure such as Extra Corporeal shock wave lithotripsy (ESWL). Results: Mean stone size was 1.36 ± 0.36 cm in group A (LL) and 1.37± 0.36 cm in group B (PL). The immediate stone clearance rate was significantly higher inGroup A (94.0%) than Group B (76.0%). Fragments proximal migration were 6.0% in LL group and 24.0% in PL group. Use of stone retrieval equipments (baskets, forceps) was 16.0% and 64.0% in LL and PL group respectively (p<0.05) and stone fragments clearance requiring auxiliary procedures were 6% and 24% (p<0.05) in LL and PL group respectively. The mean lithotripsy time 40.46 ± 19.25 min and 36.86 ± 14.83 min and mean period of post operative hospital stay was 2.32 ± 1.22 days and 2.44 ± 1.18 days in the LL and PL group respectively. Periprocedural complications like hemorrhage, mucosal disruption/ perforation were almost same in both groups. Conclusion: In this study stone clearance and fragmentation of stone in Holmium:YAG assisted ureteroscopy was significantly higher than pneumatic lithotripsy group. The need for auxiliary procedure like ESWL for proximally migrated fragments was significantly less inHolmium:YAG assisted ureterocopy compared with pneumatic lithotripsy. Bangladesh Journal of Urology, Vol. 22, No. 2, July 2019 p.160-165